Effects of inorganic nitrogen form on growth, morphology, N uptake, and nutrient allocation in hybrid Napier grass (Pennisetum purpureum × Pennisetum americanum cv. Pakchong1) - Jampeetong A. (Elsevier, 2014)
Plant cultivars with high biomass production may have a high potential for being used in integrated water treatment and plant production system. The highly productive hybrid Napier grass cultivar, Pennisetum purpureum × Pennisetum americanum cv. Pakchong1, may be a candidate species for being used in such systems. We studied the effects of inorganic nitrogen form (NH4 +, NH4NO3 or NO3 -) on growth, morphology, N uptake, water content and mineral allocation in this species under hydroponic conditions at equimolar concentrations (500μmolNL-1). Generally, the N-form significantly affected growth, biomass allocation and tissue nutrient and mineral composition of the plants. The hybrid Napier grass grew better on NH4 + compared to NO3 -, and the plants supplied with NH4 + contained three times more chlorophylls than plants supplied with NO3 - alone or NO3 - combined with NH4 +. The morphology of the plants was, however, not affected by N source, except for the shoot to root ratio, which was lower in NH4 +-fed plants. The relative water content of the leaves was lowest in the NH4 +-fed plants, but the transpiration rate was not affected, indicating that NH4 + nutrition and the associated low tissue concentration of K had negative effects on the water use efficiency of the plants.The study suggests that this hybrid Napier grass cultivar may be a new candidate species for use in integrated water treatment and plant production systems.